REPRESENTASI INNER CHILD (ANALISIS SEMIOTIKA ROLAND BARTHES PADA FILM STORY OF KALE : WHEN SOMEONE'S IN LOVE) - Mila Nur Husnul Hotimah (2022)
The phenomenon of inner child or childhood inner wounds can be experienced by anyone, both consciously and unconsciously. The film Story of Kale tells the love story of Kale and Dinda who have an unhealthy relationship due to the inner child that both parties had when they were small. This study aims to determine the representation of the inner child or childhood inner wounds in the film Story of Kale. The subject of this film is the Film Story of Kale. The method in this study uses qualitative research methods using Roland Barthes' semiotic analysis approach. The results of this study indicate that there are several indicators of the inner child description experienced by Kale and Dinda. This film shows that Kale tries to be the one who is at the forefront, often feels guilty, always hides himself, is easily suspicious, possessive, always blames himself and is afraid of losing and being abandoned by the people he loves. Then, this film also shows Dinda who has no boundaries and normalizes acts of violence mentally and physically. This study also found findings in the form of a communication parenting concept that can prevent the inner child phenomenon that occurs to Dinda and Kale in real life.